2022
DOI: 10.1007/s11356-021-17948-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between urine elements and fasting glucose levels in a community-based elderly people in Beijing

Abstract: Epidemiological studies have demonstrated that various kinds of urinary element concentrations were different between healthy, prediabetes, and diabetes patients. Meanwhile, many studies have explored the relationship between element concentration and fasting blood glucose (FBG), but the association between joint exposure to co-existing elements and FBG level has not been well understood. The study explored the associations of joint exposure to co-existing urinary elements with FBG level in a crosssectional de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Interestingly, despite not detecting statistically significant associations between plasma Zn concentrations and fasting glucose or diabetes risk, we identified a highly significant positive association between urine Zn concentrations and these parameters in our population. Many other studies have found a link between urinary Zn concentrations and glycemia/diabetes [ 94 , 155 , 156 , 157 ]. However, the mechanisms underlying this association between Zn concentrations in urine and fasting glucose, but not in plasma, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, despite not detecting statistically significant associations between plasma Zn concentrations and fasting glucose or diabetes risk, we identified a highly significant positive association between urine Zn concentrations and these parameters in our population. Many other studies have found a link between urinary Zn concentrations and glycemia/diabetes [ 94 , 155 , 156 , 157 ]. However, the mechanisms underlying this association between Zn concentrations in urine and fasting glucose, but not in plasma, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Morning first void urine samples were collected in polypropylene containers and stored at −80°C. We measured 15 urinary metals and metalloids, including Al, As, Ba, Cd, Co, Cr, Cs, Cu, Fe, Mn, Ni, Pb, Se, Sr and Zn, using inductively coupled plasma-mass spectrometry (ICP-MS) with a Nexion 300D (Perkin-Elmer SCIEX, USA), which has been described in detail in previous study ( 41 ). The urine samples were thawed at room temperature for subsequent processing.…”
Section: Methodsmentioning
confidence: 99%
“…For the identified metabolites, we conducted two-stage BKMR analysis 31 using the bkmr R package to assess the joint associations of mixed metal exposure with these metabolites and also to search for the metals responsible for such joint associations. In the first stage, we included all 17 metals in the BKMR model and conducted a component-wise variable selection method with 25,000 iterations by a Markov chain Monte Carlo (MCMC) algorithm.…”
Section: Methodsmentioning
confidence: 99%